As seen on TV: Automatic basketball video production using Gaussian-based actionness and game states recognition - Quiroga, J.; Carrillo, H.; Maldonado, E.; Ruiz, J.; Zapata, L. M. (IEEE/CVF Conference on Computer Vision and Pattern Recognition, 2020)
Automatic video production of sports aims at producing an aesthetic broadcast of sporting events. We present a new video system able to automatically produce a smooth and pleasant broadcast of Basketball games using a single fixed 4K camera. The system automatically detects and localizes players, ball and referees, to recognize main action coordinates and game states yielding to a professional cameraman-like production of the basketball event. We also release a fully annotated dataset consisting of single 4K camera and twelve-camera videos of basketball games.